(untitled) (Third Sector Social Economic Review, 2025)
White-collar workers have class and cultural characteristics that can be observed in their labour relationships, socialization processes, self-definition and self-expression. White-collar workers differ from blue-collar workers in terms of competitive working conditions and individualistic work habits that lack solidarity and collectivity. White-collar also exhibit unique characteristics in terms of cultural codes, lifestyles, self-definition, and emulation of upper classes. White-collar workers have integrated Westernization into their identities as process of status acquisition. There are signs that white-collar workers, who view traditionalism as lower-class characteristic, have chosen Westernization as cultural and class path to distinguish themselves. Furthermore, it has been observed that the Western cultural hegemony has emerged in these groups, as expressed through dynamics; individualization, secularization, higher education processes, consumption culture, and social media. This research was conducted to analyze the segment of white-collar workers in Türkiye that experiences this cultural and class alienation. This study explores the social and cultural alienation experienced by highly educated, white-collar workers in Türkiye, under the influence of Western cultural hegemony, structural contradictions created by class positions, and socialization processes. The aim of understanding the ways white-collar workers in Türkiye position themselves within society was analyzed using qualitative research methods by conceptualization of "petty whites."